2020
DOI: 10.1007/s13399-020-00788-w
|View full text |Cite
|
Sign up to set email alerts
|

Downstream processing and characterization of polyhydroxyalkanoates (PHAs) produced by mixed microbial culture (MMC) and organic urban waste as substrate

Abstract: The utilization of food waste and sewage sludge as organic substrate from urban context for the synthesis of microbial polyhydroxyalkanoates (PHAs) has been only recently investigated at pilot scale. Within this context, two stabilization methods have been found for preserving the amount of PHA intracellularly produced by open mixed microbial culture (MMC): thermal drying and wet acidification of the biomass at the end of PHA accumulation process. The extracted PHA from the two differently stabilized biomasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 41 publications
5
27
0
Order By: Relevance
“… Villano et al (2014) treated MMC with NaClO for 3 and 24 h at rt and noticed that the effect of NaClO on the purity and the molecular weight of the extracted polymer is similar regardless of the reaction time; on the other hand, the temperature of the NaClO treatment inversely impacts both the recovery and the polydispersity index: the PHA recovery decreases from rt (100%) to 85°C (50%), whereas the polydispersity index increases (giving more heterogeneous polymers) if the treatment is performed at high temperature (values around 3) or rt (values of 4–10) ( Table 5 ). Recently, Lorini et al (2020) investigated the impact of two stabilization protocols applied at the end of the accumulation phase (thermal drying at 145°C for 30 min and at 70°C overnight, and wet acidification with H 2 SO 4 ) in combination with NaClO digestion (at rt overnight) for preserving the amount and the length of PHA produced by MMC. A wet-acidification pretreatment provides three-times higher molecular weights (0.4 MDa) than a thermal pre-treatment, a recovery of 96%, and a polymer purity of 90%.…”
Section: Extraction Of Pha From Mixed Microbial Culturesmentioning
confidence: 99%
“… Villano et al (2014) treated MMC with NaClO for 3 and 24 h at rt and noticed that the effect of NaClO on the purity and the molecular weight of the extracted polymer is similar regardless of the reaction time; on the other hand, the temperature of the NaClO treatment inversely impacts both the recovery and the polydispersity index: the PHA recovery decreases from rt (100%) to 85°C (50%), whereas the polydispersity index increases (giving more heterogeneous polymers) if the treatment is performed at high temperature (values around 3) or rt (values of 4–10) ( Table 5 ). Recently, Lorini et al (2020) investigated the impact of two stabilization protocols applied at the end of the accumulation phase (thermal drying at 145°C for 30 min and at 70°C overnight, and wet acidification with H 2 SO 4 ) in combination with NaClO digestion (at rt overnight) for preserving the amount and the length of PHA produced by MMC. A wet-acidification pretreatment provides three-times higher molecular weights (0.4 MDa) than a thermal pre-treatment, a recovery of 96%, and a polymer purity of 90%.…”
Section: Extraction Of Pha From Mixed Microbial Culturesmentioning
confidence: 99%
“…Thus, in order to compare the melting behavior, the melting enthalpies (Δ H m ) of TV and C-samples, determined by DSC, are reported as a function of 3HV content in Figure 2 . Moreover, for a more complete evaluation of the 3HV content effects, results from a previous work ( Lorini et al, 2020 ) are reported, too. In this way, it was possible to have a wider range of 3HV percentage, specifically between 7.7 and 87% w/w.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, disruption of NPCM was obtained by using non-ionic surfactants as pretreatment before PHA extraction with DMC ( Colombo et al, 2020 ) and by treating the biomass with ammonia solutions at high temperatures ( Burniol-Figols et al, 2020 ). In a previous study ( Lorini et al, 2020 ), NaClO digestion was investigated for PHA recovery from MMC produced at pilot scale. More in detail, PHA was produced in the pilot plant operating in Treviso, exploiting the same feedstock (OFMSW-WAS) and operative conditions and applying the same biomass stabilization methods described in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations